Human-Computer Interaction / Selected Readings - Preece Jenny (Prentice Hall, 1989)
Provides the reader with a broad overview of both theoretical and practical issues in human - computer interaction. Preface, Acknowledgements, The Scope of Human - Computer Interaction, Interaction Tasks and Devices and Communication Skills, Psychological Aspects, Design, Evaluation, Tools for Design, Index.